2003
DOI: 10.1177/107110070302401109
|View full text |Cite
|
Sign up to set email alerts
|

Strength Analysis and Comparison of the Teno Fix® Tendon Repair System with the Two-Strand Modified Kessler Repair in the Achilles Tendon

Abstract: The Teno Fix repair was superior to the modified Kessler repair. In the Teno Fix repairs, the gap formation stress was 67% of the peak tensile stress. In comparison, in the modified Kessler repairs, the gap formation stress was 29% of the peak stress. This can be correlated to the elastic property of the modified Kessler suture and the initial tightening of the suture around the tendon fibers. The Teno Fix system is nonelastic and is fully tensioned during installation. This lends to a more gap resistant repai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 23 publications
0
22
0
1
Order By: Relevance
“…15,31 We feel this is also pertinent when evaluating studies of open versus percutaneous techniques, as many percutaneous techniques employ a six-stranded repair versus the four strands utilized in the open repairs. 12,14,19 There are numerous different suture techniques that can be utilized for tendon repair. Gebauer et al showed that the Bunnell repair was stronger than the Kessler repair.…”
Section: Discussionmentioning
confidence: 99%
“…15,31 We feel this is also pertinent when evaluating studies of open versus percutaneous techniques, as many percutaneous techniques employ a six-stranded repair versus the four strands utilized in the open repairs. 12,14,19 There are numerous different suture techniques that can be utilized for tendon repair. Gebauer et al showed that the Bunnell repair was stronger than the Kessler repair.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent article, a strength analysis and comparison of Tenofix with the widely used “modified Kessler” suture technique has been conducted on cadaver Achilles tendons [14]. Evaluation of the repairs consisted of tensile strength testing and measurement of the gap formation and peak stressed.…”
Section: Discussionmentioning
confidence: 99%
“…Cette suture est très séduisante, car elle est inerte et a montré des propriétés mécaniques supérieures aux sutures classiques, autorisant une mobilisation très précoce, permettant ainsi de réduire les adhérences et les ténolyses secondaires. Toutefois, les données cliniques in vivo sont encore peu nombreuses (20)(21)(22) et le principal inconvénient est son coût. Il est pour l'heure essentiellement utilisé pour les tendons fl échisseurs des doigts sectionnés en zone II et le tendon d'Achille.…”
Section: Chirurgie Tendineuseunclassified